The History and Future of China's Semiconductor Industry - ZHENG JUNXIONG (International Journal of Multidisciplinary Research and Studies, 2023)
This article is the first of two that will examine China's policies toward the semiconductor industry and the elements that will ultimately determine its success or failure. China's efforts to foster local semiconductor sector growth since 2014 have garnered significant attention from across the world. The goal of this series is to provide readers with a historical perspective on the numerous efforts made by the Chinese government to promote the growth of the country's homegrown semiconductor sector, beginning in the 1950s. The first section provides a background on China's previous attempts at semiconductor industrial planning, details the current goals, and analyses their performance thus far. Part two analyses why China's strategies in the past have failed, how lessons have been applied to the present, and whether or not the current approach has a chance of succeeding